Optimizing AI potential in political communication: a study of the 2024 Indonesian presidential election - Vaiqoh, Indit; Pawito,; Nurhaeni, Ismi Dwi Astuti (Penerbit Universiti Kebangsaan Malaysia, 2024)
Technological developments with the use of artificial intelligence in political communication, especially during the presidential election. AI in addition could take part in the presidential and vice-presidential elections of Indonesia in 2024. The objective of this research is to dissect artificial intelligence as a potential strategy that may be implemented during the upcoming elections within digital era. The role of artificial intelligence will be studied to assess the influence that is still being widely spread by artificial intelligence. The systematic literature review (SLR) was used as the methodology. The results of this study are of importance for supporting the assumption that it is possible to influence public opinion with AI analysis, increase voter participation and utilize AI for political campaign strategies. Steps involved in systematic literature review process include stating research objectives, developing, and validating review methods, searching literature, selecting articles for inclusion, assessing article quality, forming data findings, data analysis and reporting results. As such measures demonstrate, use of artificial intelligence (AI) in political communication can shape public discourse, serve as a campaign strategy, and offer more tailored interactions between politicians and electorate. Trust and democratic integrity call on promoting transparency, ethics, and data security above everything else. Therefore, for achieving full potential of AI in context of political communication field, political practitioners, researchers as well as policy makers can receive considerable suggestions out of this research study.